Intensity-modulated carbon-ion radiation therapy versus intensity-modulated photon-based radiation therapy in locally recurrent nasopharyngeal carcinoma: a dosimetric comparison - Wang, Lei (Cancer Manag Res, 2019)
PURPOSE: To identify the specific dose advantage of intensity-modulated carbon-ion radiation therapy (IMCT) over photon-based intensity-modulated radiation therapy (IMRT) in the treatment of locally recurrent nasopharyngeal carcinoma (NPC). MATERIALS AND METHODS: Ten patients with locally recurrent NPC underwent IMCT and IMRT planning. Target definition followed the recommendations of the International Commission on Radiation Units and Measurements (ICRU) reports no. 50, 62 and 83. The real treatment plans which were delivered to patients were designed on the Siemens Syngo planning system while the control plans for dosimetric comparison were generated from the Varian Medical Systems. The optimization constraints of the two designs were basically the same. Target coverage was evaluated using the following parameters: Dmin, Dmax, D1, D2, D50, D95, D98 and D99. Target dose distribution and conformality were evaluated using the homogeneity index and conformity index. Normal tissue sparing of organs at risk (OARs) were evaluated using Dmean, D1 and Dmax. SPSS 22.0 software was used for data analysis. RESULTS: Both IMCT and IMRT plans met clinical prescription dose requirements. Target coverage of D1, D2, D50, D95, D98, D99 were not significantly different between the two plans (P>0.05). The two plans showed satisfactory coverage of the target without significant difference. There was no significant difference in terms of the homogeneity and conformability between the two plans. Dosimetric parameters for the brain stem, spinal cord, parotid gland, optic chiasm, eyeball, lens, temporal lobe and inner ear were significantly reduced in the IMCT plan (P<0.05). CONCLUSION: As compared with photon-based IMRT, IMCT significantly reduces radiation dose to the OARs in the treatment of locally recurrent NPC while maintaining the dose coverage to the target volumes. Such a feature is particularly important for patients who experienced previous high-dose irradiation.